Promoting Terror or Sport? The Case of Qatar's International Image. (August 2016) - Samuel-Azran, Tal; Yarchi, Moran; Galily, Yair; Tamir, Ilan
Qatar's successful bid for hosting the 2022 soccer World Cup is regarded as one in a series of attempts to change Qatar's image as a terror-sponsoring state. To understand the power of hosting megasport events to rebuild a country's international image, the present study compares the coverage of Qatari sport affairs with concurrent terror-sponsoring allegations, via a sentiment analysis of coverage of Qatari affairs by three international networks (SKY, CNN, and ITV) between August 20, 2013 and December 31, 2014. Surprisingly, the analysis found that terror-related articles contained significantly more positive sentiment than articles on other issues, whereas the tone toward Qatar in sport-related articles was significantly less positive than other topics. The study illustrates the limits of using sport as a soft power strategy, and underscores the superiority of on-the-ground efforts to deflect terror allegations as a strategy for improving a country's image.